Competency building for health promotion and change in the care model - Netto, Luciana (2016)
Case study based on the theoretical and methodological framework of dialectics, aimed at analyzing competency building for health promotion, from the perspective of graduates from a nursing course and its relation to change in the care model. Interviews focused on competencies were held with ten graduates. Data were analyzed using critical discourse perspective. The results show that the competencies for health promotion, defined by two internacional consensus, were discussed in the course of the nursing education process. The discourses demonstrate that competency building for health promotion in nursing education can foster change in the care model, despite the challenges in this process. Curricular strategies like contact with reality through the immersion of students in the practical scenario since the beginning of the course and community service and research activities can contribute to competency building for health promotion in nursing education and foster the change in the care model.